The Role Of The Tanggap Karawang Application (Tangkar) In Enhancing Public Satisfaction In Karawang Regency: A Pls-Sem Approach - Hilma Mutiara Winata; Wulan Najla Attala (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The rapid development of information technology has significantly improved access to public services, including at the regional government level. In response, the Karawang Regency Government introduced the Tanggap Karawang (TANGKAR) application in 2019, designed to increase public participation by allowing citizens to report various issues such as infrastructure problems and natural disasters. This application enables faster government responses to public reports, thereby improving service delivery. Despite its potential, the implementation of TANGKAR faces several challenges, particularly in terms of accessibility for non-Android users and the lack of comprehensive public outreach. This study examines the effectiveness of the TANGKAR application in improving public satisfaction with government services in Karawang Regency. Using a quantitative approach, specifically through survey methods, this research applies the Partial Least Squares - Structural Equation Modelling (PLS-SEM) technique for data analysis. The findings reveal that the quality of electronic services provided by TANGKAR has a significant positive impact, with a 58.9% influence on public satisfaction. The measurement instruments used were proven to be valid and reliable, ensuring accurate assessments of the targeted variables. The study concludes that improving the quality of digital services is crucial for building public trust and satisfaction with local government initiatives, emphasizing the importance of continuous improvement in e-governance solutions